Iron and age-related macular degeneration - Błasiak, Janusz; Skłodowska, Anna; Ulińska, Magdalena; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Iron can be involved in the pathogenesis of age-related macular degeneration (AMD) through the oxidative stress. In siderosis, exogenous iron can cause retinal degeneration which can be also associated with elevated retinal iron levels resulting in hereditary defects in iron homeostasis. Iron is transported into the retina by the endocytosis of iron complexed with transferrin and stored in complex with ferritin. The retinal pigmented epithelium and the neuroretinal vasculature serve as blood-retina barriers and disruption of homeostasis at these barriers may result in iron overload. There is firm experimental evidence that retinas of AMD patients contain more iron than retinas of the healthy subjects, but the question whether it is the reason or a consequence of AMD remains open. Excessive iron can cause damage to protein, lipids and DNA through the generation of free radicals in the Fenton reaction. Therefore, iron may play a role in the pathogenesis of AMD as a source of free radical damage but this hypothesis has not been verified experimentally and further studies are needed to establish the relationship between disturbance in iron homeostasis and AMD.